2017
DOI: 10.1097/iyc.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Are We Missing a Vulnerable Population in Early Intervention?

Abstract: Infants with low birth weight (LBW ≤ 2,500 g) are at high risk for developmental delays, including cognitive impairments. Retrospective studies have shown that these children often have learning and/or behavioral difficulties at school age. Early evaluation and enrollment in early intervention (EI) programs may reduce the impact of these difficulties; however, many children who would benefit from such programs may not receive EI services. This study provides information on 279 children born LBW and includes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 43 publications
2
16
2
Order By: Relevance
“…Unfortunately, this national pattern of under-enrollment also holds true for infants with complicated early medical histories that place them at increased risk of experiencing developmental delays, including those born LBW (Barfield et al, 2008;Blasco, Guy, Saxton & Duvall, 2017;Litt & Perrin, 2014). State-specific research has shown that barriers to successful EI enrollment for LBW infants include lack of a formal referral tracking process and poor communication between referring providers and EI programs (Little, Kamholz, Corwin, Barrero-Castillero, & Wang, 2015).…”
Section: List Of Tablesmentioning
confidence: 99%
See 4 more Smart Citations
“…Unfortunately, this national pattern of under-enrollment also holds true for infants with complicated early medical histories that place them at increased risk of experiencing developmental delays, including those born LBW (Barfield et al, 2008;Blasco, Guy, Saxton & Duvall, 2017;Litt & Perrin, 2014). State-specific research has shown that barriers to successful EI enrollment for LBW infants include lack of a formal referral tracking process and poor communication between referring providers and EI programs (Little, Kamholz, Corwin, Barrero-Castillero, & Wang, 2015).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Furthermore, recommendations for improving EI referral outcomes for preterm and LBW infants include faxing referrals directly to EI programs rather than simply providing the family with a phone number (Jimenez, et al, 2014) and following up on referral outcomes (Little, et al, 2015). Limited data from previous research suggests some children born LBW may not be in services due to be difficulty connecting with the program or not being found eligible upon evaluation (Blasco et al, 2017). Though under-enrollment of LBW children in EI services is well documented, there is little research examining why this is the case.…”
Section: List Of Tablesmentioning
confidence: 99%
See 3 more Smart Citations